All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 112203 by mathdave last updated on 06/Sep/20
proporsedbym.njuly1970∫01ln(x+13)(x+1)(x+2)dxsolutionletI=13∫01ln(x+1)(x+1)(x+2)dxI=13∫01ln(1+x)x+1dx−∫01ln(x+1)x+2dx=A−BletA=13∫01ln(x+1)x+1dx(usingIBP)A=13[ln2(x+1)]01−13∫01ln(x+1)x+1dxA(1+13)=13ln2(2)A=∫01ln(x+1)x+1dx=13ln2(2)......(1)thenB=13∫01ln(x+1)x+2dxB=13[ln(x+2)ln(x+1)]01−13∫01ln(x+2)x+1dxletx+1=tB=13ln3ln2−13∫12ln(1+t)tdtlett=−xB=13ln3ln2−13∫−1−2ln(1−x)xdxbut∫ln(1−x)xdx=−Li2(x)B=13ln3ln2+13[Li2(x)]−1−2B=13ln3ln2+13Li2(−2)−13Li2(−1)B=13ln3ln2+13Li2(−2)+π236butI=A−B∫01ln(1+x3)(x+1)(x+2)dx=14ln2(2)−13ln3ln2−13Li2(−2)−π236mathdave(06/09/2020)
Commented by mnjuly1970 last updated on 06/Sep/20
verynice,thankyousirmathdave.gratefulforyoureffortandfavor....
Commented by Tawa11 last updated on 06/Sep/21
greatsir
Terms of Service
Privacy Policy
Contact: info@tinkutara.com